2018
DOI: 10.1039/c7dt04180b
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumour active gold(i), palladium(ii) and ruthenium(ii) complexes with thio- and selenoureato ligands: a comparative study

Abstract: We report the results of a comparative study of the biological activity of a series of gold(i), palladium(ii) and ruthenium(ii) complexes containing deprotonated thio- and selenoureato ligands. A library of compounds was prepared and characterised by spectroscopic methods and the solid-state structures of several derivatives were determined by single crystal X-ray diffraction. The in vitro activity of these compounds was evaluated in mammary and ovarian carcinoma, acute lymphatic and acute and chronic myeloid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 55 publications
1
21
0
Order By: Relevance
“…Acylselenoureas have also been reported ( Figure 1B) as hCA inhibitors [43], and are conjugated with ferrocenyl moieties as antiproliferative agents [44,45]. Palladium and ruthenium complexes of acylselenoureas have also been reported as antiproliferative against leukemia cell lines [46]. Our research group also confirmed that acylselenourea derivatives in combination with diselenide motifs present a potent and selective antitumoral activity [47].…”
Section: Introductionsupporting
confidence: 76%
“…Acylselenoureas have also been reported ( Figure 1B) as hCA inhibitors [43], and are conjugated with ferrocenyl moieties as antiproliferative agents [44,45]. Palladium and ruthenium complexes of acylselenoureas have also been reported as antiproliferative against leukemia cell lines [46]. Our research group also confirmed that acylselenourea derivatives in combination with diselenide motifs present a potent and selective antitumoral activity [47].…”
Section: Introductionsupporting
confidence: 76%
“…The 1 Ha nd 13 C{ 1 H} NMR spectra of complexes 1-4 with monodentate coordination were distinctly different to those with bidentate coordination of ligands (5)(6)(7)(8)(9)(10). The 1 HNMR spectra of complexes 5-10 featured four doubletsi nt he range of ca.…”
Section: Resultsmentioning
confidence: 95%
“…[3] Therefore, an understanding of metal-sulfur coordi-nation chemistryi si mportant to both the problemso fb iology and chemical industry. [3,4] Metal complexes of thioamides and related sulfur-containing ligandsh ave been increasingly investigated as anticancer agents, [5] catalysts [1,6] and materials. [4a] They maya ct as monodentate ligands through their sulfur or nitrogen atoms, as chelators employing both their S and N donors, or as bridging ligands for more than one metal center ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] In order to overcome these issues numerous complexes containing gold, ruthenium, palladium, even tin and titanium have been synthesized and tested. [11][12][13][14][15][16] In recent years organotin(IV) complexes are of great interest due to their potential applications in biology, medicine, catalysis, and materials science. [17][18][19][20] Many in vitro studies have shown that some organotin(IV) compounds demonstrate better anticancer potential as drugs in comparison to cisplatin.…”
Section: Introductionmentioning
confidence: 99%